Protein targeting, transport & translocation - Dalbey, Ross E.; Heijne, Gunnar von (Academic Press, 2002)
This book presents an in-depth overview on the topic of protein synthesis, covering all areas of protein science, including protein targeting, secretion, folding, assembly, structure, localization, quality control, degradation, and antigen presentation. Chapters also include sections on the history of the field as well as summary panels for quick reference. Numerous color illustrations complement the presentation of material. This book is an essential reference for anyone in biochemistry and protein science, as well as an excellent textbook for advanced students in these and related fields. Key Features * Basic principles and techniques * Targeting and sorting sequences * Protein export in bacteria * Membrane protein integration into ER and bacterial membranes * Protein translocation across the ER * Disulfide bond formation in prokaryotes and eukaryotes * Quality control in the export pathway * Import of proteins into organelles * The secretory pathway * Vesicular transport * Spectacular color throughout.